To be agents or not to be agents, that is the question: the impact of the online platforms revolution on the notion of agency under EU competition law - Luca Villani (Market and Competition Law Review, 2020)
In recent years, practitioners, commentators and competition authorities have been facing the question of whether online platforms fit the mould of a typical agent under EU competition law. The stakes are high. If online platforms could be qualified as agents, the obligations imposed on them in relation to the contracts concluded and/or negotiated on behalf of their principal(s) may fall outside Article 101 (1) TFEU. This article wishes to contribute to the debate in two ways. First, it offers an assessment of whether, under existing EU competition law, online platforms can be qualified as agents. Second, it provides a conceptual framework to determine whether the existing rules are fit for purpose.